Impact of E-Learning Media on Students’ Critical Thinking Skills at Physics Education Study Program, Almuslim University - Marnita Marnita; Rahma Rahma; Fatimah Fatimah (STKIP Singkawang, 2021)
Starting from the emergence of student boredom in taking part in the course of recovery, resulting in decreased thinking skills of students who focus more on memorizing concepts instead of understanding concepts. The researcher combines the learning model assisted by e-learning which is currently of interest. The learning model assisted by e-learning media combines principles in the learning process and technology. This study aims to determine the impact of learning with e-learning media on the improvement of critical thinking skills of students in semester III of the physics education study program. Data collection for this research was carried out in September-October 2019, this research is also the impact of the accompaniment of the PDS Grant in won by FKIP Umuslim in the 2019 budget year. Data analysis in this study used a parametric statistical test, namely the one-tail t-test. The results showed that the use of learning models assisted by e-learning media had a very positive impact on improving students' critical thinking skills. This can be seen from the acquisition of N-Gain for each student's critical thinking indicator in the medium category as many as two indicators, namely indicators providing further explanation and indicators of managing strategies, while the other three indicators get high categories, namely indicators providing simple explanations, indicators of building basic skills, and indicators set strategy or tactics.